2009
DOI: 10.1002/ejsp.721
|View full text |Cite
|
Sign up to set email alerts
|

Too late to coordinate: Contextual influences on behavioral synchrony

Abstract: The temporal coupling of behavior serves as a foundation for effective social exchange with synchronized actions moderating core components of social-cognitive functioning. Questions remain, however, regarding the precise conditions under which this form of behavioral coordination emerges. In particular, do social factors moderate the extent to which people synchronize their movements with others? Given that synchrony serves as an important non-verbal route through which interpersonal connections can be forged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(184 citation statements)
references
References 47 publications
(52 reference statements)
7
174
2
1
Order By: Relevance
“…In various situations, it has been shown that contextual cues, such as scenes surrounding the action (Iacoboni et al, 2005), presence of another agent (Sebanz, Knoblich, & Prinz, 2005) or relation to another agent (Loula et al, 2005) may have an impact on the way actions are both perceived and performed. In addition, there is evidence that even brief episodes of interaction between participants, even in simple tasks, may have an impact on their feelings about an interacting confederate (Hove & Risen, 2009;Miles, Griffiths, Richardson, & Macrae, 2010). Although individuals may differ in their ways of expression and their perceptual sensitivities, consistencies in expression and subsequent consistencies in perception can reveal underlying principles and mechanisms on which interpersonal communication is based.…”
Section: Introductionmentioning
confidence: 94%
“…In various situations, it has been shown that contextual cues, such as scenes surrounding the action (Iacoboni et al, 2005), presence of another agent (Sebanz, Knoblich, & Prinz, 2005) or relation to another agent (Loula et al, 2005) may have an impact on the way actions are both perceived and performed. In addition, there is evidence that even brief episodes of interaction between participants, even in simple tasks, may have an impact on their feelings about an interacting confederate (Hove & Risen, 2009;Miles, Griffiths, Richardson, & Macrae, 2010). Although individuals may differ in their ways of expression and their perceptual sensitivities, consistencies in expression and subsequent consistencies in perception can reveal underlying principles and mechanisms on which interpersonal communication is based.…”
Section: Introductionmentioning
confidence: 94%
“…Social orientation and motivation are malleable and affect coordination. Relevant studies have found that interacting with a late-arriving partner reduced stepping synchronization, compared with interacting with a partner who arrived on time [119], and bodily synchrony decreased during arguments compared with affiliative conversations [120].…”
Section: Social-psychological Factorsmentioning
confidence: 99%
“…Further evidence that complex brains are able to entrain to some stimuli but filter out others has come from the fact that humans are less likely to entrain a rhythmic behavior with a partner they don't like (Miles, Griffighs, Richardson, & Macrae, 2010), and that dolphins are more likely to synchronize during social than during nonsocial behaviors (Connor et al, 2006).…”
Section: Why Do Animals Vary In Entrainment?mentioning
confidence: 99%